2008
DOI: 10.3844/jmssp.2008.264.268
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of Fourth Order Linear Ordinary Differential Equations by Cubic Spline Collocation Tau Method

Abstract: Problem Statement: Many boundary value problems that arise in real life situations defy analytical solution; hence numerical techniques are desirable to find the solution of such equations. New numerical methods which are comparatively better than the existing ones in terms of efficiency, accuracy, stability, convergence and computational cost are always needed. Approach: In this study, we developed and applied three methods-standard cubic spline collocation, perturbed cubic spline collocation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…This becomes a problem of non-linear 4 th order differenial equation which has been solved by Cubic Spline Collocation Tau Method [36]. The solution uses Newton's linearizaion scheme for Taylor series expansion given by equation A6.…”
Section: A Immediately After Woundingmentioning
confidence: 99%
See 1 more Smart Citation
“…This becomes a problem of non-linear 4 th order differenial equation which has been solved by Cubic Spline Collocation Tau Method [36]. The solution uses Newton's linearizaion scheme for Taylor series expansion given by equation A6.…”
Section: A Immediately After Woundingmentioning
confidence: 99%
“…The substituion to be carried for this purpose [36] is given by equations A7-A10. The algorithm of the entire program is as follows: i. Initialize the unknowns r c ,R b , h, Z cell , K / and α. ii.…”
Section: A Immediately After Woundingmentioning
confidence: 99%
“…The work revealed that the accuracy of the results obtained by cubic B-spline were better than those obtained through finite difference method. [6] applied cubic spline collocation Tau method on linear 4th order differential equation. The method could not handle 4th order nonlinear ordinary differential equation directly.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods that can be used to solve the two point boundary value problems numerically. It had been proposed by Attili and Syam (2008); Ha (2001); Jafri et al (2009) and Taiwo and Ogunlaran (2008). Ha (2001) had solved the two-point boundary value problem using fourth order Runge-Kutta method via shooting technique.…”
Section: Introductionmentioning
confidence: 99%